2022
DOI: 10.3390/nu14142888
|View full text |Cite
|
Sign up to set email alerts
|

Whey Derivatives and Galactooligosaccharides Stimulate the Wound Healing and the Function of Human Keratinocytes through the NF-kB and FOXO-1 Signaling Pathways

Abstract: Skin repair requires the activation of keratinocytes and is mediated by controlled inflammation and cell migration and proliferation, ending with the regeneration of well-differentiated cell layers. Whey derivatives contain galactooligosaccharides (GOS), which have potential beneficial effects on wound healing due to their activity as toll-like receptor ligands, although their direct nonprebiotic effects in the skin have not yet been described. In this study, we investigated the effects of different whey-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Lactose is known to regulate insulin secretion [ 35 ]. Whey protein consumption, which contains lactose and galactooligosaccharide, is linked to NF-κB signaling [ 36 ]. A recent study found that 2′-fucosyllactose and 6′-sialyllactose, derivatives of lactose, inhibited TLR-4 activation, although lactose itself did not [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactose is known to regulate insulin secretion [ 35 ]. Whey protein consumption, which contains lactose and galactooligosaccharide, is linked to NF-κB signaling [ 36 ]. A recent study found that 2′-fucosyllactose and 6′-sialyllactose, derivatives of lactose, inhibited TLR-4 activation, although lactose itself did not [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[77] Butyrate has been shown to induce keratinocyte differentiation and improved wound closure in vitro. [78,79] Furthermore, it has recently been shown that butyrate promotes and accelerates the differentiation of epidermal keratinocytes by directly altering their metabolism, enhancing skin barrier function. [80] pMan-But treatment may induce keratinocyte differentiation and migration through a butyrate-mediated metabolic shift, ultimately improving wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-PCR primers were designed with NCBI/Primer-BLAST and synthesized by Merck (Milan, Italy). Quantitative PCR was carried out in a final volume of 25 µL using the IQ™ SYBR Green Supermix (Bio-Rad Laboratories AG, Cressier FR, Switzerland) with specific primers for the quantitation of the following human genes: cytochrome c oxidase subunit 2 (COXII; fwd 5 ′ -TCTGGTCAGCCCAACTCTCT-3 ′ , rev 5 ′ -CCTGTGATCCACCAGAAGGT-3 ′ , mitochondrial ATP synthase F0 subunit 6 (MT-ATP6; fwd 5 ′ -CCAATAGCCCTGGCCGTAC-3 ′ , rev 5 ′ -CGCTTCCAATTAGGTGCATGA-3 ′ ), mitochondrial ATP synthase F1 β subunit (ATP5B, fwd 5 ′ -GTGGGCTATCAGCCTACCCT-3 ′ , rev 5 ′ -CAAGTCATCAGCAGGCACAT-3 ′ [74], interleukin-6 (IL-6, fwd 5 ′ -GGTACATCCTCGACGGCATCT-3 ′ , rev 5 ′ -GTGCCTCTTTG CTGCTTTCAC-3 ′ ) [73], interleukin-8 (IL-8, fwd 5 ′ -GGAGAAGTTTTTGAAGAGGGCTGA-3 ′ , rev 5 ′ -TGCTTGAAGTTTCACTGGCATCTT-3 ′ ), the junction adhesion and stent protein zonula occluden-1 (ZO-1, fwd 5 ′ -AAAGAGAAAGGTGAAACACTGC-3 ′ , rev 5 ′ -TTTTAGA GCAAAAGACCAACCG-3 ′ ) [18], E-cadherin (E-cadherin, fwd 5-′ TACGCCTGGGACTCCA CCTA-3 ′ , rev 5 ′ -CCAGAAACGGAGGCCTGAT-3 ′ ) and closure protein-4 (claudin 4, CLDN4; 5' CCACAACATCATCCAAGACTTC-3 ′ , rev 5 ′ -CAGAATACTTGGCGGAGTAAGG-3 ′ [75]. PCR amplification was conducted with 1 cycle of denaturation at 95 • C for 2 min, 45 cycles of amplification including denaturation at 95 • C for 15 s, and annealing/extension at 60 • C for 30 s. Data were analyzed using the 2−DDCT, and the housekeeping gene beta-2 microglobulin (β2M, fwd 5 ′ -AGCAAGGACTGGTCTTTCTATCTC-3 ′ , rev 5 ′ -ATGTCTCGATCCCACT TAACTA-3 ′ ) was used as the reference gene to normalize the cDNA in different samples.…”
Section: Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%